Perception of Undergraduates on Government Interventions in Environmental Issues in Southwest, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study examined the perception of undergraduates on government interventions in environmental issues in Southwest, Nigeria. This study further examined the differences in the perception of undergraduates on government interventions in environmental issues in Southwest, Nigeria based on gender and ownership of University. Descriptive survey research design was adopted for the study. The population of the study comprised all university undergraduates in Southwest, Nigeria. A sample of 1752 male and female Undergraduates in Federal, State and Private Universities were used for the study. Multistage sampling procedure was employed for the sample selection. Questionnaire on Perception of Undergraduates on Government Interventions in Environmental Issues {QPUGIEI) was used in this study. The validity of the instrument was ensured through face and content validity procedures and the reliability of the QPUGIEI was established using Cronbach Alpha method and the alpha value of 0.74 was obtained. The data generated for this study were analysed using descriptive and inferential statistics. The descriptive statistics of frequency counts, mean and percentages were used to provide answers to the research question while inferential statistics of t-test and Analysis of Variance (ANOVA) were used to test the hypotheses at 0.05 level of significance. The finding of the study showed that university undergraduates had favourable perception of government interventions in environmental issues in Southwest, Nigeria, there was a significant difference in the perception of male and female undergraduates towards government interventions in environmental issues, there was a significant difference in the perception  of undergraduates towards government interventions in environmental issues based on the ownership of University. Based on the findings of this study, it was recommended that irrespective of the gender of undergraduates and ownership of the university government should intensify effort on environmental education programmes such that all undergraduates will have same favourable perception on government interventions in environmental issues.